Sex-Specific Abnormalities and Treatment-Related Plasticity of Subgenual Anterior Cingulate Cortex Functional Connectivity in Chronic Pain - Osborne, Natalie R.; Anastakis, Dimitri J.; Kim, Junseok Andrew; El-Sayed, Rima; Cheng, Joshua C.; Rogachov, Anton; Hemington, Kasey S.; Bosma, Rachael L.; Fauchon, Camille; Davis, Karen D. (Frontiers in Pain Research, 2021)
The subgenual anterior cingulate cortex (sgACC) is a key node of the descending antinociceptive system with sex differences in its functional connectivity (FC). We previously reported that, in a male-prevalent chronic pain condition, sgACC FC is abnormal in women but not in men. This raises the possibility that, within a sex, sgACC FC may be either protective or represent a vulnerability to develop a sex-dominant chronic pain condition. The aim of this study was to characterize sgACC FC in a female-dominant chronic pain condition, carpal tunnel syndrome (CTS), to investigate whether sgACC abnormalities are a common feature in women with chronic pain or unique to individuals with pain conditions that are more prevalent in the opposite sex. We used fMRI to determine the resting state FC of the sgACC in healthy controls (HCs, n = 25, 18 women; 7 men) and people with CTS before (n = 25, 18 women; 7 men) and after (n = 17, 13 women; 4 men) successful surgical treatment. We found reduced sgACC FC with the medial pre-frontal cortex (mPFC) and temporal lobe in CTS compared with HCs. The group-level sgACC-mPFC FC abnormality was driven by men with CTS, while women with CTS did not have sgACC FC abnormalities compared with healthy women. We also found that age and sex influenced sgACC FC in both CTS and HCs, with women showing greater FC with bilateral frontal poles and men showing greater FC with the parietal operculum. After surgery, there was reduced sgACC FC with the orbitofrontal cortex, striatum, and premotor areas and increased FC with the posterior insula and precuneus compared with pre-op scans. Abnormally reduced sgACC-mPFC FC in men but not women with a female-prevalent chronic pain condition suggests pain-related sgACC abnormalities may not be specific to women but rather to individuals who develop chronic pain conditions that are more dominant in the opposite sex. Our data suggest the sgACC plays a role in chronic pain in a sex-specific manner, and its communication with other regions of the dynamic pain connectome undergoes plasticity following pain-relieving treatment, supporting it as a potential therapeutic target for neuromodulation in chronic pain.